2011
DOI: 10.1002/ejoc.201100992
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)‐Mediated Intramolecular Cyclization of (Z)‐Chalcogenoenynes: Synthesis of 3‐Halochalcogenophene Derivatives

Abstract: We present our results on the cyclization of (Z)-chalcogenoenynes mediated by copper(II) salts to afford 3-halochalcogenophenes in satisfactory yields through an intramolecular 5-endo-dig cyclization. The methodology was carried out using CuCl 2 at 50°C or CuBr 2 at room temperature under an ambient atmosphere. The reaction took place under very mild re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Thus, based on the above observations and on previous reports involving electrophilic cyclization reactions, [70][71][72] the reactivity of Oxone ® [40,43,81] and reactions under ultrasonic irradiation, [77][78][79][80][81] a plausible mechanism for the formation of chalcogenophenes 7-9 from 1-3 is presented in Scheme 4.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, based on the above observations and on previous reports involving electrophilic cyclization reactions, [70][71][72] the reactivity of Oxone ® [40,43,81] and reactions under ultrasonic irradiation, [77][78][79][80][81] a plausible mechanism for the formation of chalcogenophenes 7-9 from 1-3 is presented in Scheme 4.…”
Section: Resultsmentioning
confidence: 57%
“…Generally, these compounds are prepared by the cyclization of alkynes, dienes and diynes in the presence of inorganic chalcogen species [58][59][60][61] or via the intramolecular cyclization of organochalcogen compounds [62][63][64][65][66][67][68][69] and rearrangement reactions. [70] Among these procedures, Zeni and coworkers [71] described the cyclization of (Z)-chalcogenoenynes mediated by copper(II) salts (2.0 equiv) to afford 3-halochalcogenophenes (Scheme 1b). Interested in the preparation of chalcogenophenes functionalized with organochalcogen groups, the same authors [72] reported the electrophilic cyclization of (Z)-selenoenynes with different electrophiles, such as I 2 , ICl, PhSeBr and PhSeCl using CH 2 Cl 2 as solvent (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…of nBuLi, in tetrahydrofuran (THF) at -78°C for 1 h, then treated the lithiated intermediate with an electrophilic chalcogen species. [8] Based on our recent report on the cyclization of (Z)-chalcogenoenynes to afford 3-halochalcogenophenes mediated by copper(II) salts, [9] the cyclization reaction was initially investigated by treating oalkynylbenzaldehyde 1a (1 equiv. ), chalcogenoalkyne 2a (1 equiv.…”
Section: Resultsmentioning
confidence: 96%
“…The reaction proceeds under mild conditions producing the corresponding thio- and selenophenes 4-21 efficiently (Scheme 331). 498 …”
Section: Synthesis Of Thio- Seleno- and Tellurophenesmentioning
confidence: 99%